Peculiarities of spinal epidural abscess in COVID-19 patients: a literature review - Pietro Domenico Giorgi; Giuseppe Rosario Schirò; Davide Colistra; Simona Legrenzi; Jacopo Falco; Maria Ludovica Pallotta; Giuseppe Talamonti (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2023)
During the SARS-CoV-2 pandemic, some authors described an increased incidence of primary Spinal Epidural Abscess (SEA) in COVID-19 patients with clinical and radiological peculiarities. Early recognition of this disease remains challenging, resulting in delayed diagnosis and significant morbidity and mortality. The authors performed a systematic review of the literature in PubMed, Cochrane, and Scopus about the traditional form of SEA comparing the main features related to COVID-19 SEA. The search was performed from 1990 to 2020. Magnetic Resonance Imaging with contrast is mandatory to recognize this kind of lesion in order to obtain a differential diagnosis. COVID-19 SEAs are generally active abscesses, with a large cystic component. Gadolinium-enhanced MR images can aid in the definition of the age and consistency of the abscess. A rim of tissue that enhances after the injection of gadolinium represents granulation tissue; liquid pus is associated with an area of low signal intensity on T1-weighted images. This new type of SEA in COVID-19 patients showed several differences also in clinical features. No evidence of an external infective source was found (spondylodiscitis, surgery, or percutaneous treatment). None of the patients was a drug abuser and MSSA was the only responsible pathogen. The cervicothoracic spine was the most involved site. Further studies are needed to confirm these preliminary findings.